Positive Behavioral Interventions and Family Support for Fetal Alcohol Spectrum Disorders - Petrenko, Christie L. M. (Curr Dev Disord Rep, 2015)
Although the scientific community has recognized the effects of prenatal alcohol exposure on development for over 40 years, the empirical study of positive behavioral interventions and family support programs for people with fetal alcohol spectrum disorders (FASD) has only just emerged over the last 10 to 15 years. In this time, dedicated researchers have developed innovative programs that have generally produced large effects and have been acceptable to children with FASD and their families. This body of work demonstrates that children with FASD can benefit from interventions that are appropriately tailored to their neurodevelopmental disabilities. Despite this progress, much work lies ahead to meet the significant needs of people with FASD. This review evaluates available sources of information, including theoretical and Lived Experience models, empirical evidence on existing programs, and best practice guidelines, to guide future research priorities and clinical practice. Three priorities for future intervention research are offered.